Effect of Hydration on Spontaneous Labor Outcomes in Nulliparous Pregnant Women: A Multicenter Randomized Controlled Trial Comparing Three Methods - Edwards, Rodney K.; Reed, Christine A.; Villano, Kathryn S.; Holmes, Jennifer L.; Tong, Suhong; Davies, Jill K. (American Journal of Perinatology, 2014)
Objective To evaluate the effect of mode and amount of fluid hydration during labor.Study Design The authors conducted a randomized controlled trial of uncomplicated nulliparous women in spontaneous labor at 36 weeks or more gestational age. Women were randomized to receive lactated Ringer solution with 5% dextrose at (1) 125 mL/h intravenously with limited oral intake, (2) 250 mL/h intravenously with limited oral intake, or (3) 25 mL/h intravenously with ad libitum oral intake of clear liquids. Results were analyzed by intent-to-treat analysis.Results A total of 311 out of 324 women were available for analysis. Groups 1 (n = 105), 2 (n = 105), and 3 (n = 101) above did not differ significantly for mean labor duration (11.6 ± 5.9, 11.4 ± 5.5, and 11.5 ± 5.9 hours, respectively; p = 0.998), proportion of women in labor > 12 hours (all groups 41%; p = 0.998), proportion receiving oxytocin augmentation (59, 60, and 57%, respectively; p = 0.923), or proportion delivered by cesarean (22, 17, and 17%, respectively; p = 0.309). Indications for cesarean were similar between groups. No cases of pulmonary edema, maternal aspiration, or perinatal mortality occurred.Conclusion Although apparently safe, neither increased intravenous hydration nor oral hydration during labor improves labor performance.
Keywords: labor; labor dystocia; hydration; oral hydration